Assessing the Variation in Maize Water Footprint Under Different Tillage Practices: A Case Study from Jilin Province, China - Bo Li; Lijie Qin; Mingzhu Lv; Yongcai Dang; Hang Qi (Agriculture)
Studying the impact of different tillage practices on crop water consumption can help us identify optimal tillage practice choices. The traditional tillage (TT) and conservation tillage (CT) methods are the dominant practices in Jilin Province, China. Few studies have explored the differences in crop water consumption between TT and CT. To address this knowledge gap, this study utilized maize as its research object and employed the water footprint (WF) as the indicator to assess crop water consumption under TT and CT. This study aimed to investigate when differences in water consumption between TT and CT appear and whether the differences are significant. The results of this study demonstrated that the total WF under CT (339.65 m3 t−1) was less than that under TT (378.19 m3 t−1), and the spatial difference was distinct. The total WF exhibited a clear change under different CT durations. At the initial stage of CT implementation, the total WF decreased slightly compared to that under TT. With an increase in CT duration, the total WF was significantly reduced. The findings of this study demonstrate that CT is an effective measure to ensure sustainable crop production and that it could lead policymakers to choose CT to reduce water consumption.